67 Developing a strategy to improve the integration of international medical graduates into the great ormond street hospital for children. (4th October 2017) - Dimitriades, K; Parish, EJ; Poison, J; Clarke, V; Hemingway, C; Sharma, S
Abstract : Background: International Medical Graduate (IMG) describes all doctors that have qualified in a country outside the United Kingdom. Doctors qualifying abroad choose employment at Great Ormond Street Hospital for Children (GOSH) for many reasons. These doctors have varying levels of experience and qualifications as well as individualised social and family responsibilities. Project: IMG were identified on Intrepid data software by the Human resources department and an electronic survey was distributed to this group. This survey consisted of nineteen questions in the form of Likert scale answers and free text comments. Results: Seventy-two out of one-hundred-sixty-one (44.7%) doctors responded to the survey. Forty-six respondents were between the ages of 30 and 39 whilst fourteen were between the ages of 40 to 49. IMGs had an average of 12.6 years' experience (5–23 years) and for 39/60 (65%) of respondents, this was their first job within the NHS. IMGs reported UK integration as mostly difficult (40.3%) or neutral (27.8%). Themes that make integration easy include: social factors, information packages and completion of GMC registration. Factors that make integration harder include: different culture, different hospital systems and administrative load. Integration into GOSH was considered easier for 51.4% but difficult for 30.5% of respondents. Factors considered to encourage integration include: previous NHS experience, colleagues and English proficiency. Factors that make integration harder include: administrative load, poor orientation and computerised systems. Difficulties encountered include, correct salary level employment, finding a school, accommodation and banking. Sixty percent (36/60) reported lack of clarity around career progession to become an NHS consultant. Further exploration revealed a need for education regarding paths to consultant registration. Conclusions: International medical graduates face multiple challenges when moving to the UK. A strategy to assist with their integration is required and is best developed according to the particular healthcare environment. The following strategies have been identified to assist IMG integration into working at GOSH: Improving pre–onboarding information and communication. Improving the induction program and tailoring towards IMG's specific needs. Development of an educational package for IMG. Raising institutional awareness for the difficulties faced by IMG. Continuous monitoring through collection of data.